2017
DOI: 10.1038/s41598-017-16409-y
|View full text |Cite
|
Sign up to set email alerts
|

Active Sites of M(IV)-incorporated Zeolites (M = Sn, Ti, Ge, Zr)

Abstract: M(IV)-incorporated zeolites have recently aroused wide interest due to outstanding catalytic effects while their active sites remain largely elusive. Here periodic density functional theory calculations are conducted finding that active sites are determined jointly by identity of M(IV) ions, topology of zeolites, type of framework species and choice of T sites. All M2(IV) active sites in BEA zeolites are penta-coordinated with chemisorption of one water while subsequent water molecules that form only H-bonds p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 72 publications
3
19
0
Order By: Relevance
“…The most stable water complex is the O-down water complex on the T4 site, with an adsorption energy of -38 kJ/mol. The average water adsorption energy on 1Ge-UTL models amounts to -28±6 kJ/mol (in line with previously reported values for Ge-BEA 47 ), which is approximately 2-3 kJ/mol higher than the average water stabilization in the purely siliceous UTL framework. In addition, including temperature effects in AIMD simulations confirms that water affinity to germanium Lewis sites is lower than that of a purely siliceous sample (see details about AIMD simulations and their analysis in Section 2.3 of SI, Figures S8-S10 in particular).…”
Section: Ge-poor Utlsupporting
confidence: 90%
See 1 more Smart Citation
“…The most stable water complex is the O-down water complex on the T4 site, with an adsorption energy of -38 kJ/mol. The average water adsorption energy on 1Ge-UTL models amounts to -28±6 kJ/mol (in line with previously reported values for Ge-BEA 47 ), which is approximately 2-3 kJ/mol higher than the average water stabilization in the purely siliceous UTL framework. In addition, including temperature effects in AIMD simulations confirms that water affinity to germanium Lewis sites is lower than that of a purely siliceous sample (see details about AIMD simulations and their analysis in Section 2.3 of SI, Figures S8-S10 in particular).…”
Section: Ge-poor Utlsupporting
confidence: 90%
“…After calculating the adsorption energies of single water molecules adsorbed near the Ge atom at a particular T site and in a similar position in the purely siliceous model of UTL (0Ge-UTL model), we determined that the adsorption affinity near an isolated germanium atom was relatively low (Table S2). In our modelling, we identified two types of water adsorption complexes: i) O-down complexes (close Ow-Ge contact in the range of 2.34-2.83 Å) in which germanium acts as a Lewis acid site, extending its coordination sphere to five, 47 and ii) H-down complexes, which show no specific germanium-water interaction and are characterized only by one or two close Hw-Ofr contacts (2.04-2.52 Å). These structures are similar to local minima of water adsorbed in the purely siliceous UTL framework, not only in geometry but also in adsorption energies (see Table S2 and Figure S7b).…”
Section: Ge-poor Utlmentioning
confidence: 99%
“…Yang and co‐workers conducted a series of studies and concluded that three different framework M(IV) sites should co‐exist in M(IV)‐incorporated zeolites – see Scheme . In addition to the perfectly tetrahedral M(IV) sites, the other two are (O 3 Si) 3 MOH defects that are created through the hydrolysis of the Si‐O‐M(IV) linkages.…”
Section: Dehydration Of Glucose By Heterogeneous Catalystsmentioning
confidence: 99%
“…Different framework Sn(IV) species within zeolites that are referred to as: Left: Perfectly tetrahedral Sn(IV) sites, Middle: Defects with Lewis acidity and Right: Defects with Brønsted acidity …”
Section: Dehydration Of Glucose By Heterogeneous Catalystsmentioning
confidence: 99%
“…Moreover, impressive studies 12,[21][22][23] show that transition-metal-based QSH insulators possess intrinsic and beyond s−p band inversion, such as p−p, 24 d −p 12 as well as d −d , 21 due to the strong electronic interaction instead of SOC. 25 Such intrinsic band inversion not originating from SOC greatly enrich the family of QSH insulators and enlarge their promise for nanoscale device applications, and also stimulate the further investigations on interesting phenomena, such as transition in correlated Dirac fermions 26 and interaction induced topological Fermi liquid. 27 It is noteworthy that transition-metal-based 2D materials usually holding the intrinsic layered characteristic, such as transition metal-based dichalcogenides (such as MoS 2 , TiS 2 , TaS 2 ), 28 transition-metal carbides (MXenes), 29 transition-metal nitrides (such as TiNCl) 30 as well as transition-metal Halides (e.g., ZrBr), 21 can be achieved from corresponding 2D intrinsic layered materials via simple exfoliation or chemical vapor deposition, without any chemical functionalization or lattice distortion or applying strain, which is beneficial for the future experimental preparation for monolayers in the field of QSH insulators.…”
mentioning
confidence: 99%